(untitled) (Journal of Obstetrics and Gynaecology of Eastern and Central Africa, 2024)
Background: Interstitial cystitis is a debilitating condition with a rising prevalence due to increased research and diagnostic criteria. Interstitial cystitis falls under the category of urologic chronic pelvic pain syndrome and is a diagnosis of exclusion. Interstitial cystitis or bladder pain syndrome (BPS) is characterized by chronic inflammation. Common symptoms include chronic pelvic pain, pressure, or discomfort perceived to be related to the urinary bladder accompanied by other urinary symptoms, such as persistent urge to void or urinary frequency in the absence of confusable diseases (hypersensitive bladder symptoms). The true burden of interstitial cystitis is underestimated, and the economic burden of the disease is due to multiple office visits and an increase in direct medical costs. Case presentation: A 59-year-old para 2+0 (2 previous scars) postmenopausal with a 1-year history of frequency (up to eight episodes) nocturia with low abdominal pain. Her urinalysis profile, urea, electrolytes and creatinine, and ultrasound and computed tomography of the kidneys, ureters and bladder, pap smear, and random blood sugar tests were unremarkable. Cystoscopy was hemorrhagic with biopsy histology showing ulcerated bladder mucosa with numerous plasma cells, eosinophils, and neutrophils in the lamina propria no atypia, with fibrosis and dilated capillaries in the lamina propria. On follow-up she had a recurrence of pain symptoms with a cystoscopy biopsy, seven months later showing plasma cell infiltrate with ulceration of the overlying urothelium, and congestion of the blood vessels. She was not neoplastic and was put on antihistamine, nonsteroidal antiinflammatory drugs, and solifen. Conclusion: Prompt diagnosis and treatment of interstitial cystitis will reduce the burden of disease associated with multiple outpatient visits and unnecessary use of antibiotics. The mainstay of management is oral and intravesical treatment with surgery in refractory cases.